Analysis of bulletproof vest made from fiber carbon composite and hollow glass microsphere (HGM) in absorbing energy due to projectile impact - Anhar, Muhammad P.; Sutikno, S.; M. S. M., Sani (IOP Publishing, 2019)
Bulletproof vest serves as a barrier and simultaneously absorbing the impact energy of a projectile shot from a firearm so it could not injure the users. Manufacture of lighter bulletproof vests with good absorbent of impact energy, is expected, because it supports the mobility and safety of its users. In this study, a composite composed of an epoxy matrix with a 16% Hollow Glass Microsphere (HGM) and carbon fiber reinforce to be implemented in a bulletproof vest. The objective of this research is to analyze the bullet-proof vests made of epoxy matrix composites with reinforcement in the form of HGM and carbon fiber through simulation with finite element method. Simulations with Ansys conducted in accordance with NIJ Standard 0101.06 from the U.S. Department of Justice, where the projectile initial velocity of 426 m/s for the category IIIA class weapon with a kinetic energy of projectile amounted to 528.37 Joules. The simulation with Ansys was performed by varying the thickness of bulletproof vests to obtain optimum thickness. The outcome of this research is a bulletproof vest that absorbs the impact energy of the projectile, so that the energy transmitted to the body is smaller than 170 Joules. Having obtaining the optimum thickness of bulletproof vest, an experimental verification will be performed to validate the simulation results. In the simulation results showed that a bullet proof vest with a thickness of 20 mm has been able to meet the standards of Major General Julian S. Hatcher, a U.S. Army ordnance expert with great energy generated at 138.77 Joules.